Question
upstudy study bank question image url

1. If the equation formed by decreasing each root of \( a x^{2}+b x+c=0 \) by ' 1 ' is \( 2 x^{2}+8 x+2=0 \), the values of \( \frac{a}{b} \) and \( \frac{b}{c} \).

Ask by Nichols Boone. in India
Jan 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\[ \frac{a}{b} = \frac{1}{2} \quad \text{and} \quad \frac{b}{c} = -1 \]

Solution

To solve the problem, let's follow these steps: 1. **Understand the Transformation of Roots:** - The quadratic equation \( a x^{2} + b x + c = 0 \) has roots \( r_1 \) and \( r_2 \). - Decreasing each root by 1 gives new roots \( r_1 - 1 \) and \( r_2 - 1 \). - The new quadratic equation with these roots is \( 2 x^{2} + 8 x + 2 = 0 \). 2. **Formulate the New Equation:** - To find the new equation when each root is decreased by 1, substitute \( x = y + 1 \) in the original equation. - This substitution transforms the original equation \( a x^{2} + b x + c = 0 \) into: \[ a (y + 1)^2 + b (y + 1) + c = 0 \] - Expanding this, we get: \[ a y^2 + (2a + b) y + (a + b + c) = 0 \] - This must equal the new equation \( 2 y^{2} + 8 y + 2 = 0 \). Therefore, we equate the coefficients: \[ \begin{cases} a = 2 \\ 2a + b = 8 \\ a + b + c = 2 \end{cases} \] 3. **Solve for the Coefficients:** - From the first equation: \( a = 2 \). - Substitute \( a = 2 \) into the second equation: \[ 2(2) + b = 8 \Rightarrow 4 + b = 8 \Rightarrow b = 4 \] - Substitute \( a = 2 \) and \( b = 4 \) into the third equation: \[ 2 + 4 + c = 2 \Rightarrow c = -4 \] 4. **Calculate the Required Ratios:** - \( \frac{a}{b} = \frac{2}{4} = \frac{1}{2} \) - \( \frac{b}{c} = \frac{4}{-4} = -1 \) **Final Answer:** \[ \frac{a}{b} = \frac{1}{2} \quad \text{and} \quad \frac{b}{c} = -1 \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve this problem, let's denote the roots of the original quadratic equation \( ax^2 + bx + c = 0 \) as \( r_1 \) and \( r_2 \). According to the problem, the new roots after decreasing each root by 1 are \( r_1 - 1 \) and \( r_2 - 1 \). Given that these new roots correspond to the quadratic equation \( 2x^2 + 8x + 2 = 0 \), we can find the sum and product of the roots from this equation. From Vieta's formulas, we know: - The sum of the new roots \( (r_1 - 1) + (r_2 - 1) = -\frac{b}{a} - 2 \) - The product of the new roots \( (r_1 - 1)(r_2 - 1) = \frac{c}{a} - \frac{b}{a} + 1 \) For the equation \( 2x^2 + 8x + 2 = 0 \): - The sum of the roots \( -(8/2) = -4 \) - The product of the roots \( 2/2 = 1 \) From the sum of the new roots, we set up the equation: \[ r_1 + r_2 - 2 = -4 \implies r_1 + r_2 = -2 \] From the product of the new roots, we have: \[ (r_1 - 1)(r_2 - 1) = r_1r_2 - (r_1 + r_2) + 1 = 1 \] Substituting \( r_1 + r_2 = -2 \) into the product equation gives: \[ r_1r_2 + 2 + 1 = 1 \implies r_1r_2 = -2 \] Now, we apply Vieta's relationships back: For the original equation \( ax^2 + bx + c = 0 \): 1. \( r_1 + r_2 = -\frac{b}{a} \) 2. \( r_1r_2 = \frac{c}{a} \) We already have \( r_1 + r_2 = -2 \) and \( r_1r_2 = -2 \): Thus, \(-\frac{b}{a} = -2 \implies \frac{b}{a} = 2\) which gives us \(\frac{a}{b} = \frac{1}{2}\). Additionally, we have: \(\frac{c}{a} = -2 \implies \frac{b}{c} = \frac{b/a}{c/a} = \frac{2}{-2} = -1\). In conclusion: \[ \frac{a}{b} = \frac{1}{2}, \quad \frac{b}{c} = -1. \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy